Confocal Microscopy and Molecular-Specific Optical Contrast Agents for the Detection of Oral Neoplasia - Carlson, Alicia L. (2007)
Using current clinical diagnostic techniques, it is difficult to visualize tumor morphology and architecture at the cellular level, which is necessary for diagnostic localization of pathologic lesions. Optical imaging techniques have the potential to address this clinical need by providing real-time, sub-cellular resolution images. This paper describes the use of dual mode confocal microscopy and optical molecular-specific contrast agents to image tissue architecture, cellular morphology, and sub-cellular molecular features of normal and neoplastic oral tissues. Fresh tissue slices were prepared from 33 biopsies of clinically normal and abnormal oral mucosa obtained from 14 patients. Reflectance confocal images were acquired after the application of 6% acetic acid, and fluorescence confocal images were acquired after the application of a fluorescence contrast agent targeting the epidermal growth factor receptor (EGFR). The dual imaging modes provided images similar to light microscopy of hematoxylin and eosin and immunohistochemistry staining, but from thick fresh tissue slices. Reflectance images provided information on the architecture of the tissue and the cellular morphology. The nuclear-to-cytoplasmic (N/C) ratio from the reflectance images was at least 7.5 times greater for the carcinoma than the corresponding normal samples, except for one case of highly keratinized carcinoma. Separation of carcinoma from normal and mild dysplasia was achieved using this ratio (p<0.01). Fluorescence images of EGFR expression yielded a mean fluorescence labeling intensity (FLI) that was at least 2.7 times higher for severe dysplasia and carcinoma samples than for the corresponding normal sample, and could be used to distinguish carcinoma from normal and mild dysplasia (p<0.01). Analyzed together, the N/C ratio and the mean FLI may improve the ability to distinguish carcinoma from normal squamous epithelium.